MENGGAGAS PEMBANGUNAN HUKUM NASIONAL BERBASIS RELIGIUS: STUDI TERHADAP PELUANG KONTRIBUTIF HUKUM ISLAM DALAM ARAH PEMBANGUNAN HUKUM NASIONAL - Achmad Irwan Hamzani (Jurnal Hukum Islam, 2012)
Since the Independence Day of Indonesia, Islamic law has played a significant role in shaping Indonesian society, as Muslims contributed largely to the composition of the Indonesian population. This article starts with the critical analysis of the national law, Pancasila as philosophy of the Indonesian legal system, to the rises of Islamic law in Indonesia. How Islamic law has been transformed over its rich history will also be examined, namely the implementation of Islamic law in Indonesia. The paper tries to give readers a broader understanding of Islamic legal concepts, as this will enable them to understand the differences and similarities between the national and Islamic legal system. Moreover, it will provide readers with enough knowledge to analyze applications of Islamic law, specifically, to the practices and implementation of this law in Indonesia in order to comprehend the unique ‘model’ of Islamic law to develop national law in this developing nation.